Análise de um Filtro Ativo em Paralelo com Cicloconversores e Filtro Passivo - Ferreira, Célio Geraldo (2008)
In the steel industry non linear loads are frequently used such as cycloconverters for rolling mills. This kind of load influences the power quality of the supply network, resulting in distortion in the system voltage. In order to improve the power quality of the grid, passive filters are commonly used. However, a passive filter can present some drawbacks, mainly when the plant is under expansion or the operating conditions change. These drawbacks of the passive filter can be alleviated by the combined use of active and passive filters, and by appropriately coordinating their operations. That is, of the harmonic currents generated by the cycloconverter, part is absorbed by the active filter, and another by the passive filter. This provides a good harmonic compensation over the entire operating range for the varying spectrum harmonic current frequencies generated by the cycloconverter. This work analyzes a real electrical power supply of a steelmaking rolling mill, in the present conditions, as well as in a scenario of plant expansion. A digital simulation model, consisting of a passive filter, active filter, cycloconverter load and power supply system was developed, followed by a study to investigate the combined use of passive and active filters, mainly to assess their effectiveness to compensate the harmonic components and, consequently, to improve the plant power quality level.